Uji Viabilitas Isolat Bakteri Penambat Nitrogen Halotoleran pada Komposisi Bahan Pembawa yang Berbeda - Nida Uli Al-Azmiya; Fiqriah Hanum Khumairah; Mieke Rochimi Setiawati; Tualar Simarmata (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2021)
The process of microbial inoculation into plant biomass which will be decomposed needs a suitable carrier material to facilitate the application of the microorganisms to be used. Halophilic bacteria are a type of microorganism that can survive high salt levels by maintaining an osmotic balance. The bacterial consortium is a collection of bacteria that work together to form a community, to produce a significant product. The experiment aims to determine the effect of carrier composition on inoculant viability. The experiment was carried out at the laboratory CV. Bintang Asri Arthauly Bandung, West Java, Indonesia. The study used a non factorial randomized design with three replications. The treatment design to be tested in this experiment, among others: c1: Peat 50% + Compost 50% + Nutrition 0%, c2: Peat 50% + Compost 45% + Nutrition 5%, c3: Peat 50% + Compost 40% + Nutrition 10%, c4: Peat 50% + Compost 25 % + Biochar 25% + Nutrition 0%, c5: Peat 50% + Compost 22.5% + Biochar 22.5% + Nutrition 5%, c6: Peat 50% + Compost 20% + Biochar 20% + Nutrition 10%, c7: Peat 50% + Compost 20% + Biochar 20% + Dolomite 5% + Guano 5% + Nutrition 0%, c8: Peat 50% + Compost 17.5% + Biochar 17.5% + Dolomite 5% + Guano 5 % + Nutrition 5%, c9: Peat 50% + Compost 15% + Biochar 15% + Dolomite 5% + Guano 5% + Nutrition 10%. The results of the second stage experiment showed that the c8 composition had the best viability in all carrier compositions.